Does the Type of Extracorporeal Shock Therapy Influence Treatment Effectiveness in Lateral Epicondylitis? A Systematic Review and Meta-analysis. Issue 10 (October 2020) - Yoon, Seo Yeon; Kim, Yong Wook; Shin, In-Soo; Moon, Hyun Im; Lee, Sang Chul
Abstract: Background: Extracorporeal shock wave therapy (ESWT) has been used in various musculoskeletal disorders, including lateral epicondylitis. However, in 2005, a meta-analysis of randomized controlled trials showed that ESWT provides minimal or no benefit in terms of pain and function in patients with lateral epicondylitis. Since the review, several randomized controlled trials including different types of ESWT such as radial type for lateral epicondylitis have been published. Investigations of the effect modifiers such as symptom and follow-up duration on the effects of ESWT on lateral epicondylitis have not been performed. Questions/purposes: (1) Does ESWT reduce pain and improve grip strength in patients with lateral epicondylitis? (2) Which type of ESWT, radial or focused, is more effective? (3) Is the duration of symptoms associated with the efficacy of ESWT for lateral epicondylitis? (4) Do improvements in pain scores remain in patients with longer follow-up? Methods: The PubMed, Embase, and Cochrane Central Register of Controlled Trials databases were searched up to July 2019 for articles published in English or Korean. Studies were included if patient allocation was randomized, the sample was composed of patients with lateral epicondylitis, interventions were ESWT (focused or radial), comparison group only received sham stimulation or no additional treatment, and the study outcome was pain intensity or grip strength. The quality of the evidence was assessed using the Cochrane risk of bias tool. Twelve studies including 1104 participants fulfilled the inclusion criteria and were included in the meta-analysis. The mean difference for pain reduction and improvement in grip strength was calculated. Results: The meta-analysis showed no clinically important difference in the VAS score (2.48 ± 7.55 versus 3.17 ± 9.78, mean difference -0.68 [95% confidence interval -1.17 to -0.19]; p = 0.006) and grip strength (38.02 ± 70.56 versus 34.85 ± 108.26, mean difference 3.33 [95% CI 0.93 to 5.73]; p = 0.007) after ESWT relative to the comparison group's score. Even though radial ESWT showed more improvement than focused, the mean difference for VAS did not exceed the minimal clinically important differences threshold. There were no clinically important effects on the VAS scores of patients with lateral epicondylitis (2.78 ± 5.57 versus 3.92 ± 6.29, mean difference -1.13 [95% CI -1.84 to -0.42]; p = 0.002) and focused ESWT did not improve pain in patients with lateral epicondylitis. In the subgroup analysis, ESWT was effective in patients with a symptom duration of more than 6 months (2.28 ± 8.48 versus 3.31 ± 11.81, mean difference -0.95 [95% CI -1.75 to -0.15]; p = 0.02) but not for those with shorter symptom duration. The effects did not last beyond 24 weeks (2.52 ± 9.19 versus 3.34 ± 5.93, mean difference -0.82 [95% CI -2.57 to 0.93]; p = 0.36). Conclusions: ESWT did not show clinically important improvement in pain reduction and grip strength. Radial ESWT, symptom duration of longer than 6 months, and short follow-up duration (less than 24 weeks) were related to better effects. Further studies are needed to determine the appropriate protocol and elucidate the effects according to the intervention type and specific disease condition. Level of Evidence: Level I, therapeutic study.